A scoping review of lymphatic filariasis research in Zambia - Shirley, Hugh; Orriols, Adrienne M.; Hogan, Dylan; Chimfwembe, Kingford; Bwalya, Alinaswe; Sibbuku, Kaala; Lardizabal, Janelle; Tillotson, Sophie; Grifferty, Grace; Coombs, Philip Espinola; Wamai, Richard (Frontiers in Tropical Diseases, 2024)
Lymphatic filariasis (LF) is a neglected tropical disease caused by microfilariae of the Wuchereria and Brugia genus and spread by mosquitoes. Chronic infection and associated morbidity leads to poor psychosocial and economic outcomes. LF elimination programs have been underway in many countries, including Zambia, a country in Sub-Saharan Africa where LF has long been endemic. Zambia has made great progress in moving towards elimination through a multipronged strategy involving mass drug administration, regular surveillance, and morbidity management and disease prevention. This scoping review aims to capture the breadth of literature published on LF in Zambia to support further research into the disease that may support ongoing elimination efforts, research gaps, and funding opportunities. PRISMA-ScR and JBI scoping review guidelines were used in the design and conduct of this scoping review, leading to 475 full-text articles screened and included in data analysis, with analyzed information including publication year, journal, study theme, study type, citation number, and funding sources. The resulting screen found many articles focused on disease epidemiology in Zambia, but less research on vectors, treatment and prevention. Therefore, we conclude there may be opportunities to better understand this disease in the Zambian context through filling in these research gaps.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/7W62G